Protective role of testis-specific peroxiredoxin 4 against cellular oxidative stress - Tasaki, Eisuke (J Clin Biochem Nutr, 2017)
Peroxiredoxin (PRDX), a newly discovered antioxidant enzyme, has an important role in hydrogen peroxide reduction. Among six PRDX genes (PRDX1–6) in mammals, PRDX4 gene is alternatively spliced to produce the somatic cell form (PRDX4) and the testis specific form (PRDX4t). In our previous study, PRDX4 knockout mice displayed testicular atrophy with an increase in cell death due to oxidative stress. However, the antioxidant function of PRDX4t is unknown. In this study, we demonstrate that PRDX4t plays a protective role against oxidative stress in the mammalian cell line HEK293T. The PRDX4t-EGFP plasmid was transferred into HEK293T cells; protein expression was confirmed in the cytoplasm. To determine the protective role of PRDX4t in cells, we performed image-based analysis of PRDX4t-EGFP expressed cells exposed to UV irradiation and hydrogen peroxide using fluorescent probe CellROX. Our results suggested that PRDX4t-EGFP expressed cells had reduced levels of oxidative stress compared with cells that express only EGFP. This study highlights that PRDX4t plays an important role in cellular antioxidant defense.